The role of law in social control: Analytical theoretical research - Saleem Patros Elias; Sherwan Othman Rasool (QALAAI ZANIST JOURNAL, 2024)
This research, a theoretical and analiytical research, studies the role of law as a major necessity and a means of social control, which defines rights and duties, regulates relationships, and controls the behavior of individuals for the survival and continuity of society. The research consists of several sections, where the first section deals with the general framework of the research, including the problem, importance, and objectives of the research. While the second section consists of scientific concepts and research methodology. The third section refers to the prospectives of philosopher and thinkers about the role of law in the process of social control. The fourth section deals with the importance of law and its objectives, while the fifth section consists of the research findings, suggestions, and recommendations.